Examining the impact of mobile app features on impulsiveness: the moderating role of 'pay-more-get-more' promotion. (23rd May 2019) - Prashar, Sanjeev; Gupta, Priyanka; Parsad, Chandan; Vijay, T. Sai
With the exponential growth of smart phone users, mobile applications (apps) have become an essential platform for electronic retailers. Considering the research gap in the existing literature on shoppers' impulsiveness in the context of mobile medium, the present study investigates the effect of various antecedents in triggering impulsiveness in mobile apps shopping and inducing continuous purchases. The pioneer study used the structural equation modelling to test the hypothesised research model. It is observed that antecedents like effort expectancy, apps atmosphere, user experience and user satisfaction, price and discount have influence on impulse buying intention of shoppers. The study also confirms the moderating role of 'pay-more-get-more' promotional offers. The paper concludes with theoretical and managerial implications.